PENGARUH UPAH, PERAN SERIKAT PEKERJA TERHADAP KESEJAHTERAAN PEKERJA MELALUI UNJUK RASA PADA SERIKAT PEKERJA NASIONAL PSP PT SAI APPAREL INDUSTRIES - Eldy, Elifaz; Pradhanawati, Ari; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Welfare workers are influenced by several factors, such as good wages and role of trade unions.Workers so do the rallies to fight them welfare. This study aims to identify and explain the effect of wages and the role of trade unions on the welfare of workers. the effect of rallies on welfare. Object of this research PT Sai Apparel Industries which all workers are members of the National Labor Union. This type of research is explanatory research. The technique of collecting data using interviews, questionnaires and observation. The conclusion from this study is that wages and role of trade unions effect on workers welfare. Based on the conclusion that the company needs to increase the amount of compensation in the form of allowances. Unions need to enhance the role to be the center of information for workers. Besides, the government should review the minimum wage policy is based on the necessities of life for single workers.